Mass Mortality of Water Buffalo Bubalus bubalis (Artiodactyla: Bovidae) in Indonesia: A Two-Decade Retrospective - Diah Komala Sari; Arfan Abrar; Nur Arifah; Gusti Ayu Widayanti; Muhammad Diki Wahyu Arisandi; Ina Aprillia; Muhammad Iqbal (BIO PALEMBANICA, 2025)
Water Buffalo Bubalus bubalis are an essential livestock species in Indonesia. However, mass mortality events have been reported in recent years, highlighting the need for better understanding and management of the causes of these cases. This study presents the first comprehensive retrospective analysis of B. bubalis mortality events in Indonesia between 2010 and 2025. Data were compiled from scientific reports, government records, media coverage, and citizen science platforms. A total of 34 documented events were identified, with most attributed to infectious diseases, particularly Septicemia Epizootica (SE) caused by Pasteurella multocida. Environmental stressors such as floods and droughts, along with parasitic infections like Surra, were also contributing factors. Mortality peaks occurred in 2013 and 2023, each involving hundreds of deaths in single outbreaks. These findings underscore the urgent need for region-specific disease surveillance, vaccination programs, and improved husbandry practices.